Spatial analysis of Aedes aegypti larval distribution in the Ilha do Governador neighborhood of Rio de Janeiro, Brazil - Souza-Santos, R; Carvalho, M S (Cadernos de saúde pública, 2000)
This study aims to help expand knowledge on Aedes aegypti in Rio de Janeiro, based on spatial analysis of the mosquito's breeding sites in the neighborhood of Ilha do Governador, Rio de Janeiro, from June 1992 to July 1994. Use of spatial analysis techniques is proposed for vector surveillance and control. Information obtained from the number of dwellings per block that were used for the analysis. A smoothing method, a Gaussian Kernel, was used in the spatial distribution analysis. Breaks in National Health Foundation intervention activities were observed between cycles 4 and 5 and 5 and 6, respectively, followed by increases in vector density and vector-positive areas. Permanently positive areas, like slums and a military compound, display the persistence of favorable environmental conditions for oviposition and larval growth, indicating flaws in the vector control program. Although Kernel is an exploratory analytical method involving subjective interpretation, it provides easy and fast visualization of sites subject to different degrees of risk, unaffected by existing political and administrative territorial apportionment.